Information, Communication and Knowledge for Lean Healthcare Management Guidelines, a Literature Revision (Revista do LabDGE - UFF, 2023)
The objective is to identify the management of information, communication and knowledge in Emergency Care Units (ECU). The method was a lexical and semantic analysis using VOSViewer, categorization of the results for a qualitative and cross analysis of the approaches on the subject. With the results of the practical application of the Lean Project in the ECU in 50 units it was possible to establish criteria and a parameter for knowledge management in this health area. The results categorize the publications in four central themes in healthcare: leadership and governance; quality in health; technology and information; Lean. The information flow is presented as a means, not an end activity and this is confirmed when the articles limit themselves to highlight the means of communication, applications or devices used for the dissemination of information, without further deepening of steps such as data collection, validation and valuation of information in health environments. The human factor is the main agent of change, because it needs clarity that the use of information and communication technologies do not make its final activity impossible, but it is a facilitating, agile and effective tool in the conduct of their work activities.